Diagnóstico, evaluación de alternativas, análisis y cálculos hidráulicos de las redes matrices del sistema de acueducto de Quibdó, Chocó (2013)
The project corresponding to the "Studies, alternatives and challenges for the optimization of the aqueduct and sewerage systems of the municipality of Quibd6 in the Department of Chocó was presented by the Quibd Consortium 2011, for which the author of the present work worked for the Companies. Public of Quibdó in Aguas del Atrato Liquidation in December 2012. Taking into account the scope of the work carried out, this document presents the additional considerations and analyzes carried out on the La Playita - Tanque elevated mining area line, in order to propose other alternatives for the operation and operation of this line of driving.